Modulation of rat skeletal muscle branched-chain alpha-keto acid dehydrogenase in vivo. Effects of dietary protein and meal consumption. - Block, K P (1987)
The effects of dietary protein on the activity of skeletal muscle branched-chain alpha-keto acid dehydrogenase (BCKAD) were investigated. BCKAD is rate-limiting for branched-chain amino acid (BCAA) catabolism by muscle; its activity is modulated by phosphorylation-dephosphorylation. In rats fed an adequate protein (25% casein) diet, BCKAD was approximately 2% active postabsorptively and increased to 10% or 16% active after a 25% or 50% protein meal, respectively. Prolonged feeding of a 50% protein diet increased postabsorptive BCKAD activity to 7% with further increases to 40% active postprandially. On a low protein (9% casein) diet BCKAD remained approximately 2% active regardless of meal-feeding. Dose-dependent activation of BCKAD by intravenous leucine in postabsorptive rats was blunted by a low protein diet. We conclude that excesses of dietary protein enhance the capacity of skeletal muscle to oxidize BCAA, muscle conserves BCAA when protein intake is inadequate, and skeletal muscle may play an important role in whole-body BCAA homeostasis.